Spatial Distribution and Tree Cover of Hillside and Ravine Forests in Uruguay: The Challenges of Mapping Patchy Ecosystems - Toranza, Carolina; Lucas, Christine; Ceroni Acosta, Mauricio Bruno (Agrociencia Uruguay, 2019)
The mapping and monitoring of forest ecosystems on a national scale is key to their management and conservation. Native forests in Uruguay are considered given their importance for biodiversity and ecosystem services. Here we evaluate the spatial distribution of the land cover class ‘hillside and ravine forest’ -a subclass of native forest characterized by patches and transition zones with native grasslands- using Landsat images (30 x 30 m) from 2014 and 2015 and high-resolution images from Google Earth. To evaluate spatial heterogeneity within hillside forests, we then used high-resolution spot images of 1 km2 from 1998-2012 to evaluate differences in the normalized difference vegetation index (ndvi) among canopy coverage categories. The hillside and ravine forest class were characterized as a composite cover class with an average canopy coverage of 69 ± 23%, variability of wich was reflected in ndvi values. The total area of this class in 2015 was estimated as 334,480 ha, somewhat less than an earlier 2008 estimate (384,240 ha). Among the potential errors in delineating hillside forests using Landsat images, there was the classification of «forest» in areas characterized by grassland and a tree canopy cover <25 %. This potential error in delimitation at broader scales led to the overestimation of hillside and ravine forest area in southeastern Uruguay, but an underestimation in northern Uruguay. Our study highlights the large discrepancies in the estimation of the distribution of hillside and ravine forest at different spatial scales, and also indicates the potential of ndvi to evaluate the heterogeneity of this forest within the same cover class.